Insight into mtDNA diversity of wild forest musk deer (Moschus berezovskii) in Shanxi Province mountains - Luyao Hai; Yixin Li; Xianna Lan; Zhengwei Luo; Chao Pei; Defu Hu (Scientific Reports)
Abstract Shanxi Province is the northernmost distribution range of Chinese forest musk deer (Moschus berezovskii), with wild populations scattered across Zhongtiao (ZT), Lüliang (LL), and Taiyue (TY) mountain ranges. Using line transect surveys and local guide assistance, coupled with infrared camera data, this study systematically collected fecal samples from wild forest musk deer from five nature reserves across the three mountain ranges. Genetic diversity was analyzed using the mtDNA control region, which yielded 129 effective sequences of 656 bp and 20 distinct haplotypes. Haplotype and nucleotide diversities were 0.916 and 0.01505, respectively, indicating a relatively high overall genetic diversity in the studied populations. Significant genetic differentiation was observed between the Lüliang–Taiyue (LLTY) and ZT mountain range populations, with most of the genetic variation existing within the populations. No significant correlation was detected between the geographical and genetic distances of the samples, which may have resulted from historical agricultural activities in Shanxi impeding gene flow among populations. Therefore, genetic exchange programs are recommended to improve the genetic diversity and population fitness of forest musk deer in this region to facilitate their recovery and growth.